Late postnatal mother-to-child transmission of the human immunodeficiency virus through breastfeeding: analysis of infant cases of previously seronegative mothers infected during lactation - Barcellos, Ana Carolina; Rossetto, Nathalia Zorze; Rodrigues, Cristina de Oliveira (Brazilian Journal of Sexually Transmitted Diseases, 2017)
Introduction: Vertical transmission is considered an indication of human immunodeficiency virus (HIV) infection in children aged below five years. The main postnatal category of exposure is through breastfeeding. When maternal infection occurs in early postnatal period, the risk of infant infection is even higher, due to a high maternal viral rate in this period. Objective: To evaluate HIV infection in infants assisted by the Pediatric Infectology Service of Hospital de Clínicas da Universidade Federal do Paraná, emphasizing the cases where vertical transmission occurred postnatally through breastfeeding. Methods: Transversal, analytical and descriptive study, with quantitative and qualitative approach, analyzing all HIV-infected patients aged 0 to 16 years, assisted between 2010 and 2015. The analysis of category of exposure was carried out by a general protocol, followed by a specific protocol for cases where transmission was suspected to have occurred due to late postnatal transmission through breastfeeding, aiming at understanding pediatric and maternal characteristics. Results: Records from 122 patients were analyzed, with 95.0% of mother-to-child-transmission cases. Between these cases, 11 (9.5%) were considered possible or confirmed late postnatal transmission through breastfeeding, having the presence of breastfeeding as a requirement. By the time of diagnosis, 72.7% presented symptoms of HIV infection. In 45.4% of these cases, mother and children were diagnosed at the same time, and 72.7% of mothers were infected sexually. Conclusion: Mother‑to‑childtransmission was the main responsible for infant infection and there was a significant prevalence of late postnatal transmission through breastfeeding in our sample. Moreover, the severity of infant symptoms, the moment of diagnosis and mother’s category of exposure highlight a gap on HIV prevention, and the importance of finding prophylactic measures and scientific improvement in order to reduce HIV transmission through breastfeeding.